Effective Teaching Approaches in Islamic Religious Education Learning - Chumayroh; Cahyadi, Ani (RADINKA JAYA UTAMA PUBLISHER, 2025)
This article analyzes effective teaching approaches and strategies in Islamic Religious Education (PAI) to shape learners' character and morals. This is the first research to explore teaching methods, such as normative, historical, psychological, and contextual approaches, as well as active, problem-based, project, collaborative, and technological learning strategies, especially literature reviews. The aim of this study is to identify and highlight some publications that analyze various approaches and effective teaching strategies in Islamic Religious Education.The research uses a literature review, collecting article from databases such as Google Scholar, ResearchGate, and Scopus. The main results show that contextual approaches and problem-based strategies effectively connect religious theories with students' daily life practices. However, challenges such as time constraints, gaps in theory and practice, and low utilization of technology are still obstacles. The main conclusion is the importance of relevant and adaptive teaching innovations to improve the effectiveness of PAI learning. This article recommends the integration of technology and the preparation of contextualized materials as solutions to these challenges.